(3OjhGf GHf GdSGYGJjs - (3Ydj Hf eMeO Hf QSJe Hf gQOhR, CHh GdMSf, HgGA GdOjf GHf GdSGYGJj,J (B604 (3g` s ((3Ydj Hf eMeO GdeQJVj GdShOj GdRjOj GdYOdj s)
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO ajgG(B: (3ShGHb OeYj GdMeQ ajgG NajQI hef bHd cGfJ aj Gdcejf ef GdTgH s
(3BNQgG (B:s
(3Ef JNGda aj CfgG GdTeS aGfXQ fhQgG ChLHJ bdi GdCbeGQ s
(3HJQJjHgG GVWQGHs
(3hjJdhg eNJGQGJ TYQjI ChdgG ef OjhGf GHf GdeYdes
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B330 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B62s
Keywords: (3GdCOHs